Materials surface damage and modification under high power plasma exposures - Garkusha, I. E.; Makhlaj, V. A.; Byrka, O. V.; Taran, V. S.; Voitsenya, V.; Malykhin, S. V.; Herashchenko, S. S.; Surovitskiy, S. V.; Nowakowska-Langier, K.; Sadowski, M. J.; Skladnik-Sadowska, E.; Terentyev, D. (My University, 2018)
Influence of powerful plasma impacts on several materials used for the construction of energy systems, i.e. different grades of steels as well as tungsten coatings, has been discussed. Irradiations of these materials with hydrogen and helium plasma streams have been performed in several high-current-pulse and quasi-stationary plasma accelerators which provided the variation of a power load upon the exposed surface as well as changes of the particle flux in wide ranges: the energy flux density in the range of 1-25 MJ/m2, particle flux - up to 1026-1029 ion/m2s, the plasma stream velocity - up to about 500 km/s, and the pulse duration in the range of 1-250 μs. A response of the investigated materials to extreme plasma loads, which are relevant to transient events in fusion reactors, is briefly discussed. It is demonstrated that a broad combination of mechanisms of powerful plasma interactions with various materials includes not only a surface damage caused by different erosion mechanisms, but under certain conditions it may also result in a significant improvement of material properties in the nearsurface surface layer of several tens μm in thickness. Some improvement of the structure and substructure of such a layer may be caused by the high-speed quenching, the shock wave formation and material alloying with plasma- and coating-species. The creation of unique surface structures and a considerable improvement of physical and mechanical properties of different materials can be achieved by the pulsed plasma alloying, i.e. pre-deposited coating modifications and mixing caused by the impacting plasma streams.